2005
DOI: 10.1016/j.jconrel.2005.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The role of cavitation in acoustically activated drug delivery

Abstract: Pluronic P105 micelles are potential candidates as chemotherapy drug delivery vehicles using ultrasonic stimulation as a release trigger. Acoustic power has been previously shown to release two anthracycline agents from these polymeric carriers. In this study, an ultrasonic exposure chamber with fluorescence detection was used to examine the mechanism of doxorubicin release from P105 micelles. Acoustic spectra were collected and analyzed, at the same spatial position as fluorescence data, to probe the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 44 publications
5
140
2
Order By: Relevance
“…Specifically, the size of the ultrasonically-targeted tumor in the leg of rat was reduced while a non targeted tumor in the other leg was less affected [12]. More recently, we have shown that there is a strong correlation between acoustically-triggered Dox release from both stabilized and non-stabilized micelles, and the emergence of a subharmonic peak in acoustic spectra suggesting a strong role of cavitation in the release mechanism [3]. A follow up study showed that more drug release was observed from non-stabilized micelles, when compared to stabilized micelles [13].…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Specifically, the size of the ultrasonically-targeted tumor in the leg of rat was reduced while a non targeted tumor in the other leg was less affected [12]. More recently, we have shown that there is a strong correlation between acoustically-triggered Dox release from both stabilized and non-stabilized micelles, and the emergence of a subharmonic peak in acoustic spectra suggesting a strong role of cavitation in the release mechanism [3]. A follow up study showed that more drug release was observed from non-stabilized micelles, when compared to stabilized micelles [13].…”
Section: Introductionmentioning
confidence: 80%
“…The same drug concentration was also prepared in PBS. Additional details have been published earlier [3,4].…”
Section: Drug Encapsulation In Pluronic Micellesmentioning
confidence: 99%
See 3 more Smart Citations